MODERN SCHOOLCHILDREN’S VIEWS ABOUT THE LEVEL OF THEIR OWN DIGITAL LITERACY - Kalinichenko С.А.; Shmigirilova И.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The article understands the problem of developing digital literacy of a modern schoolchild as a necessary competence in the era of the digital economy. Аim of the article is to empirically explore school students’ ideas about the level of their own digital literacy, to formulate principles, the implementation of which in teaching computer science to schoolchildren will ensure the development of a set of digital literacy components. The study, based on an analysis of scientific literature, summarizes approaches to defining the concept of “digital literacy”. Schoolchildren’s ideas about the level of development of their digital literacy were obtained based on a survey of two age groups of schoolchildren: grades 5-8 and grades 9-11. It is concluded that there are differences in the levels of proficiency in the components of digital literacy among different respondents and the uneven representation of each of these components in an individual student. The role of school informatics in increasing the level of digital literacy of schoolchildren is substantiated. The research materials can be useful in determining ways to develop digital literacy of modern schoolchildren